What every engineer should know about software engineering - Laplante, Phillip A.; Kassab, Mohamad (Boca Raton : CRC Press, Taylor & Francis Group, 2023)
"This book offers a practical approach to understanding, designing, and building sound software based on solid principles. Using a unique Q&A format, it addresses the issues that engineers need to understand in order to successfully work with software engineers, develop specifications for quality software, and learn the basics of the most common programming languages, development approaches, and paradigms. The new edition is thoroughly updated to improve pedagogical flow and emphasize new software engineering processes, practices, and tools that have emerged in every software engineering area. It is aimed at a wide range of engineers across disciplines who work with software"--
The profession of software engineering -- Software properties, processes, and standards -- Software requirements engineering -- Software architecture -- Designing software -- Software construction -- Software quality assurance -- Managing software projects and software engineers -- Software engineering: roadmap to the future -- Appendix A: Software requirements for a wastewater pumping station wet well control system (rev. 02.01.00) -- Appendix B: Software design for a wastewater pumping station wet well control system (rev. 02.01.00) -- Appendix C: Object models for a wastewater pumping station wet well control system -- Appendix D: Unified modeling language.
OCLC-licensed vendor bibliographic record.
Keywords: Software engineering